DIGITAL BISEXUALITY: THE SEMIOTICS OF ONLINE SEXUAL IDENTITY - Madison, Nora (AoIR Selected Papers of Internet Research, 2015)
This paper analyzes the practices of signifying ‘bisexuality’ across multiple online spaces. Central to this paper is a discussion of the significance of the efforts to represent bisexuality within existing socio-political systems of representation for sexual orientation. Cultural norms ideologically shape the intelligibility of representation; bisexuality is often misinterpreted when read within the dominant binaries of heterosexuality and homosexuality in Western European culture. As Stuart Hall (1996) clearly articulates, “all identities are about questions of using the resources of history, language and culture in the process of becoming rather than being” (p. 4). This work addresses how users adapt visual, textual, and hyperlinked information in online spaces to signify bisexuality. I suggest these practices be understood as ‘technologies of visibility.’